Chemical Composition, Anti-neuraminidase, and Anti-atherogenic Activities of the Essential Oil from two Varieties of Alpinia zerumbet Leaves - Upadhyay, Atul; Chompoo, Jamnian; Ahmad, Rizwan; Tawata, Shinkichi; Pieters, Luc (Journal of Food Science and Technology Nepal, 2014)
The present study describes the chemical composition and neuraminidase (NA) enzyme inhibition and anti-atherogenic properties of the essential oils (EO) of two varieties of Alpinia zerumbet (alpinia) leaves. A total of forty eight compounds were identified using GC-MS studies, which showed that tairin variety contained more compounds than shima variety. The EO inhibited NA in a dose-dependent manner with IC50 values of 41.5 ± 2.7 and 62.3 ± 3.1 μg/ml for tairin and shima varieties, respectively. Furthermore, the kinetic studies of NA inhibitions revealed that tairin EO exhibited slow, time-dependent and mixed type of inhibitions. It seems that the minor components of tairin EO have better inhibitory properties. In order to assess the anti-atherogenic activities of EO, inhibitions of 15-lipoxygenase (15-LOX) and low density lipoprotein (LDL) oxidation were investigated. The results also showed that tairin EO had better activities against 15-LOX and LDL oxidation (IC50 = 235 ± 7, and 133 ± 3 g/ml), than shima EO (IC50 = 465 ± 12, and 195 ± 5 μg/ml). Finally, the acute toxicity analysis using Caenorhabditis elegans showed that LC50 values were more than 2500 μg/ml. These findings suggest that tairin EO could be a possible candidate for further investigations in search for bioactive compounds against neuraminidase. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10563 J. Food Sci. Technol. Nepal, Vol. 7 (22-30), 2012